ACR Appropriateness Criteria® Vomiting in Infants - Alazraki, Adina L; Rigsby, Cynthia K; Iyer, Ramesh S; Bardo, Dianna M E; Brown, Brandon P; Chan, Sherwin S; Chandra, Tushar; Dietrich, Ann; Falcone, Jr, Richard A; Garber, Matthew D; Gill, Anne E; Levin, Terry L; et al. (Journal of the American College of Radiology, 2020)
Vomiting in infants under the age of 3 months is one of the most common reasons for parents to seek care from their doctor or present to an emergency room. The imaging workup that ensues is dependent on several factors: age at onset, days versus weeks after birth, quality of emesis, bilious or nonbilious vomiting, and the initial findings on plain radiograph, suspected proximal versus distal bowel obstruction. The purpose of these guidelines is to inform the clinician, based on current evidence, what is the next highest yield and most appropriate imaging study to pursue a diagnosis. The goal is rapid and accurate arrival at a plan for treatment, whether surgical or nonsurgical. The following modalities are discussed for each variant of the symptom: plain radiography, fluoroscopic upper gastrointestinal series, fluoroscopic contrast enema, ultrasound of the abdomen, nuclear medicine gastroesophageal reflux scan. The American College of Radiology Appropriateness Criteria are evidence-based guidelines for specific clinical conditions that are reviewed annually by a multidisciplinary expert panel. The guideline development and revision include an extensive analysis of current medical literature from peer reviewed journals and the application of well-established methodologies (RAND/UCLA Appropriateness Method and Grading of Recommendations Assessment, Development, and Evaluation or GRADE) to rate the appropriateness of imaging and treatment procedures for specific clinical scenarios. In those instances where evidence is lacking or equivocal, expert opinion may supplement the available evidence to recommend imaging or treatment.